Drug interaction in Geriatrics - OSCANOA, TEODORO (2004)
Elderly patients have three main characteristics that differentiate them from other population groups: polypathology, polypharmacy and physiologic changes related with aging that alter drugs’ pharmocokinetic and pharmacodynamic. These three factors increase drug-drug interactions (DDI) in frequency and severity. Drug-drug interactions are part of drug related problems (DRP) in elderly patient that need to be studied in regards to its epidemiology and adequate strategies to prevent it. Prudent use of medications and vigilant drug monitoring are essential to avoid adverse drug reactions caused by drug-drug interactions.